PENGARUH PENGGUNAAN METODE CARD SORT TERHADAP MOTIVASI BELAJAR SISWA - Yesi Susilawati; Rabbiyanur Lubis (Turats, 2021)
The teaching and learning process is essentially the delivery of messages from the introduction tothe recipient. In learning fiqh, so that the learning materials provided are easier to understand, learningmethods are needed that help the delivery process. Because the learning method is a component thatcan support the realization of student learning activities so as to achieve goals that can increasestudent learning motivation.The problem formulation of this research is the effect of the Card Sortmethod on students’ learning motivation in Fiqh subjects at MTs Miftahul Ulum Bekasi. This studyaims to determine the effect of the Card Sort method on students’ learning motivation in Fiqh subjectsat MTs Miftahul Ulum Bekasi. The research method used is a Quasi Experimental research method.In the experimental class using the Card Sort method and in the control class using the Discussionmethod. The instrument in this study used a before and after questionnaire. The research sample was20 students for the experimental class and 20 students for the control class. The results showed thatthe experimental class, namely students’ learning motivation using the Card Sort method, obtainedan average result before of 64.85 and an average result of 80.tcount = 7,994 > ttable = 1.73 with asignificant level of 0.05 then H1 is accepted and H0 is rejected, which means there is an influence CardSort method on students’ learning motivation in learning Fiqh. While the control class showed thatstudents’ learning motivation using the discussion method was obtained the average result before was44.10 and the average result after was 66.20. Thenhypothesis testing was carried out using the t test,so that obtained tcount = 7.426 > ttable = 1.73 with a significant level of 0.05 then H1 is accepted andH0 is rejected. Based on these results, it can be seen that students’ learning motivation using the CardSort method has a greater effect than using the discussion method in the control class.